(3GdeegO GdcHjQ GdLGeY deYGfi GdSff hGdCMcGe heG JVefg ehWC eGdc ef Gdabg hGdBKGQs - (3YeQ Hf Ydj Hf jhSa GdYKeGfj GdQjaj, GHf GdRgQGA GdhQjGZdj,J (B710 (3g` s
(3ChdgG (B:s
(3HGH eG LGA ai GdJbi s
(3BNQgG (B:s
(3CHh NQGT GdSdei dg UMHI Je GdSaQ Gdehai NeSjf ef cJGH GdeegO GdcHjQ jJdhg Ef TGA Gddg YR hLd ai GdSaQ GdMGOi hGdNeSjf HGH eG LGA ai WdH GdYde s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B56s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdMOjK h GdeUWdMs